Metformin in neoadjuvant systemic therapy of breast cancer patients with metabolic syndrome - Liubota, Roman; Cheshuk, Valeriy; Zotov, Olexyy; Vereshchako, Roman; Anikusko, Mykola; Liubota, Iryna; Gur'yanov, Vitaliy (Archive of Oncology, 2018)
BackgroundThe aim of this prospective randomized trial was to investigate the influence of metformin on the effectiveness of neoadjuvant systemic therapy in breast cancer patients with metabolic syndrome.Patients and methodsThe study included 72 patients (from 31 to 77 years of age) who received neoadjuvant systemic treatment for stage II-III breast cancer at the National Medical University named after O.O Bogomolets, Municipal City Clinical Oncological Center, Department of Oncology, Kyiv during 2010 - 2014. Metabolic syndrome was diagnosed in all patients according to the International Diabetes Federation criteria. They were divided in two groups: group 1 that included 36 patients with metabolic syndrome and breast cancer who did not intake metformin during neoadjuvant systemic therapy, and group 2 that included 36 patients with metabolic syndrome and breast cancer who received metformin with neoadjuvant systemic therapy.ResultsComplete clinical response was identified in 2 (6 %) patients from group 1 and 10 (27.5 %) patients from group 2. Overall clinical response rate (cCR + cPR) was achieved in 28 (77.5 %) patients treated with metformin compared to 9 (25 %) patients from group 1. A stable disease was observed in 19 (53 %) patients who were not taking metformin. The rate of pathological complete response was 26.5 % (9 patients) in the metformin group and 6 % (2 patients) in the non-metformin group.ConclusionsCombined neoadjuvant systemic anticancer therapy of breast cancer patient with metabolic syndrome with metformin has a higher clinical and pathological overall response rate than treatment without metformin.
Keywords: breast cancer; metabolic syndrome; neoadjuvant systemic therapy; metformin